Small organic molecule-functionalized upconversion nanoparticles for detection and bioimaging - Gu, Bin (2018)
In recent years the bio-detection and bio-imaging are hot research areas, more and more probes have been reported to monitor intracellular and intercellular substances, which are highly sensitive, high-resolution and low-cost. Though they have many advantages, these probes have some main limitations such as short lifetime, small penetration depth, damage to the samples and autofluorescence.Therefore new probes should be developed to overcome these shortcomings.On the other hand, upconversion nanoparticles (UCNPs) have got considerable interest and have many potential applications in this field. Compared with conventional fluorescent probes, UCNPs have many advantages: chemical stability, non-autofluorescence from bio-samples, large light penetration depth, long lifetime (millisecond scale) and less damage to samples.